The Rule of Zakon: The Criminal Cassation Department and Legality in Late Imperial Russia, 1866–94. Issue 4 (1st September 2013) - BHAT, GIRISH
Abstract : This article addresses the legal culture of late imperial Russia as reflected in the work of its highest criminal appeals court, the Criminal Cassation Department. The texts of the decisions rendered by Criminal Cassation, pre‐revolutionary Russia's approximate version of the U.S. Supreme Court in criminal law, demonstrate a commitment to legality expressed in a close reading of, and adherence to, statute ( zakon ). This zakonnost ', in contrast to many of the other vital "legalities" described in late imperial historiography, was not motivated principally by political, cultural, or social ideology; rather, it was the product of a Westernized, maturing jurisprudence, dedicated to law in itself as a calling and task beyond extralegal considerations, and may be regarded as an example of Richard Wortman's notion of "Russian legal consciousness" in practice.